2016
DOI: 10.17014/ijog.4.1.1-10
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotopes and Hydrochemistry Approach for Determining the Salinization Pattern of Shallow Groundwater in Alluvium Deposit Semarang, Central Java

Abstract: A groundwater study has been conducted in the Semarang City in August 2014, aiming to determine the source of shallow groundwater salinization using stable isotopes (18 O, 2 H) and water chemistry approach, and supported by local hydrogeological data. A number of shallow groundwater samples were taken at several locations with a depth of 0-35 m. Based on geological data, shallow groundwater of Semarang alluvium is dominated by insertion of sand-gravel and sandy-clay with average porosity of around 56.0 %. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Whereas, the stable isotopes 18 O and 2 H are present in water in the form of 1 H 2 18 O and 1 H 2 H 16 O compounds (Satrio et al, 2017). These two isotopes are very sensitive to physical processes such as evaporation and condensation, therefore to prevent this the sampling was carried out in the following manner.…”
Section: Field Sampling and Laboratory Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, the stable isotopes 18 O and 2 H are present in water in the form of 1 H 2 18 O and 1 H 2 H 16 O compounds (Satrio et al, 2017). These two isotopes are very sensitive to physical processes such as evaporation and condensation, therefore to prevent this the sampling was carried out in the following manner.…”
Section: Field Sampling and Laboratory Testingmentioning
confidence: 99%
“…Hydroisotope method using 2 H and 18 O has been chosen because of its relatively low cost of analysis (Irawan, 2009;Alam et al, 2014). The advantage of using the stable isotopes δ 18 O and δ 2 H compared to other isotopes is that the content of these stable isotopes in rainwater shows a linear relationship in the form of a global meteoric water line (Satrio & Sidauruk, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Interaction of groundwater-seawater traced using δ 2 H and δ 2 O isotope analysis and hydrochemical methods. Both isotopes used as a marker in identifying the source of groundwater in the aquifer, the possibility could be coming from rain, deeper or shallower groundwater, seawater, fossil water, or magmatic water ( [21]; [31]). The isotope analysis in Riau province studied by [32] was the first to define the Local Meteoric Water Line (LMWL) found that the reference value for LMWL in this area is δ 2 H = 7.6 δ 18 O + 10.5 (r 2 = 0.921).…”
Section: )mentioning
confidence: 99%
“…The salinity of groundwater occurred in major cities and found to intruded the groundwater wells, both shallow and deep wells [20]. It is occurred not only on the wells that closed to the shoreline [21] but also in further sites [22]. One of the major provinces in Indonesia, Riau, has also faced saltwater intrusion and upconing problems, particularly in the coastal areas and in the islands.…”
Section: Introductionmentioning
confidence: 99%
“…1), the findings could not reveal any geological factors that caused the groundwater contamination in the area. (Hadian et al, 2014(Hadian et al, , 2015Satrio, 2015Satrio, , 2017Barkah, 2015). …”
Section: Geological Mapping Of Rancaekek and Sayangmentioning
confidence: 99%